Synthetic Aspects and Selected Properties of Graphene - C. N. R. Rao; K. S. Subrahmanyam; H.S.S. Ramakrishna Matte (Nanomaterials and Nanotechnology, 2011)
Graphene has generated great sensation owing to its fascinating properties with possible potential applications. This two-dimensional material exhibits half-integer quantum Hall effect and an ambipolar electric field effect, along with ballistic conduction of charge carriers. In this article, we provide a overview on some aspects of graphene devoting the special attention to synthesis, functionalization, self-assembly, surface properties, gas adsorption and fluorescence quenching ability of graphene. Graphenes with varying number of layers can be synthesized by using different strategies. Graphene can be functionalized by different means in order to disperse it in various solvents. We also present the self-assembly of graphene at the liquid-liquid interface besides its surface properties including adsorption of hydrogen, carbon dioxide and methane. The remarkable property of graphene of quenching fluorescence of aromatic molecules is shown to be associated with photo-induced electron transfer.